PERTANGGUNGJAWABAN DOKTER DAN MODEL PENYELESAIAN PERKARA MALPRAKTIK MEDIK DI INDONESIA - Tri Handayani (Universitas Islam Kadiri, 2020)
There is an international tendency to divert medical dispute from the litigation model (in court settlement) to the out-of-court dispute models (out of court settlement) which leads to the win-win situation of the paradigm. This paradigm has actually started to be adopted in Indonesia only the implementation is still not encouraging. Law Number 36 Year 2009 on Health (Health Law) provides that disputes arising out of negligence of health personnel must be resolved through mediation (Article 29). This provision has not fully become the reference of the public and law enforcement officers related to the settlement of medical disputes in Indonesia. The tendency of patients in Indonesia to prosecute doctors through legal channels is still quite high. This is further exacerbated by the attitude of law enforcement officers who seem less concerned with the provisions of Article 29 of Law Number 36 Year 2009 on Health above. The application of mediation means in the dispute of medical disputes as required by article 29 of the Health Law faces a number of obstacles in the field. One of the obstacles is the lack of implementing regulations that explain how such mediation mechanisms should technically be run. There are a number of laws and regulations governing mediation such as Supreme Court Regulation No. 1 of 2008 on Mediation Procedures in Courts and Law No. 30 of 1999 on Arbitration and Alternative Dispute Settlement. Supreme Court Regulation No. 1 of 2008 regulates the court-annexed mediation while Law Number 30 Year 1999 regulates the arbitration and Alternative Dispute Resolution (ADR) institutions. In addition, there are also some institutions that perform mediation functions such as: Consumer Dispute Settlement Agency (BPSK), Ombudsman, and Badan Pengawas Rumah (RSB). All such institutions are deemed relevant for the settlement of medical disputes. It is thus quite confusing at the operational level.